CHARACTERIZATION OF PARACETAMOL ORALLY DISINTEGRATING TABLET USING GELATIN 1% AND 2% AS BINDER AND POLYPLASDONE XL-10 10% AS DISINTEGRANT (Prepared by Freeze Drying Method) - Nawatila, Roisah (2014)
Paracetamol, a para-aminophenol derivative, is usually given per oral as antipyretic and analgesic for the treatment of fever1. Pediatric